Single-molecule imaging and manipulation of biomolecular machines and systems - Iino, Ryota; Iida, Tatsuya; Nakamura, Akihiko; Saita, Ei-ichiro; You, Huijuan; Sako, Yasushi (Biochimica et biophysica acta, 2018)
Biological molecular machines support various activities and behaviors of cells, such as energy production, signal transduction, growth, differentiation, and migration. We provide an overview of single-molecule imaging methods involving both small and large probes used to monitor the dynamic motions of molecular machines in vitro (purified proteins) and in living cells, and single-molecule manipulation methods used to measure the forces, mechanical properties and responses of biomolecules. We also introduce several examples of single-molecule analysis, focusing primarily on motor proteins and signal transduction systems. Single-molecule analysis is a powerful approach to unveil the operational mechanisms both of individual molecular machines and of systems consisting of many molecular machines. Quantitative, high-resolution single-molecule analyses of biomolecular systems at the various hierarchies of life will help to answer our fundamental question: “What is life?” This article is part of a Special Issue entitled "Biophysical Exploration of Dynamical Ordering of Biomolecular Systems" edited by Dr. Koichi Kato. •Single-molecule imaging reveals operation mechanisms of motor proteins.•Single-molecule manipulation reveals mechanical properties of motor proteins.•Single-molecule imaging reveals signaling mechanisms of proteins in living cells.